Reactive Oxygen Species Partly Mediate DNA Methylation in Responses to Different Heavy Metals in Pokeweed - Jing, Minyu; Zhang, Hanchao; Wei, Mingyue; Tang, Yongwei; Xia, Yan; Chen, Yahua; Shen, Zhenguo; Chen, Chen (Frontiers in Plant Science, 2022)
DNA methylation is a rapid response strategy promoting plant survival under heavy metal (HM) stress. However, the roles of DNA methylation underlying plant adaptation to HM stress remain largely unknown. Here, we used pokeweed, a hyperaccumulator of manganese (Mn) and cadmium (Cd), to explore responses of plant to HM stress at phenotypic, transcriptional and DNA methylation levels. Mn- and Cd-specific response patterns were detected in pokeweed. The growth of pokeweed was both inhibited with exposure to excess Mn/Cd, but pokeweed distinguished Mn and Cd with different subcellular distributions, ROS scavenging systems, transcriptional patterns including genes involved in DNA methylation, and differentially methylated loci (DML). The number of DML between Mn/Cd treated and untreated samples increased with increased Mn/Cd concentrations. Meanwhile, pretreatment with NADPH oxidase inhibitors prior to HM exposure markedly reduced HM-induced reactive oxygen species (ROS), which caused reductions in expressions of DNA methylase and demethylase in pretreated samples. The increased levels of HM-induced demethylation were suppressed with alleviated ROS stress, and a series of HM-related methylated loci were also ROS-related. Taken together, our study demonstrates that different HMs affect different DNA methylation sites in a dose-dependent manner and changes in DNA methylation under Mn/Cd stress are partly mediated by HM-induced ROS.